Immunization With Recombinant Haemonchus contortus Y75B8A.8 Partially Protects Local Crossbred Female Goats From Haemonchus contortus Infection - Tian, Xiaowei; Lu, Mingmin; Bu, Yongqian; Zhang, Yang; Aimulajiang, Kalibixiati; Liang, Meng; Li, Charles; Yan, Ruofeng; Xu, Lixin; Song, Xiaokai; Li, Xiangrui (Frontiers in Veterinary Science, 2022)
Haemonchus contortus Y75B8A.8 (Hc8) derived from H. contortus excretory-secretory (ES) products was identified as a functional inhibitor of goat interleukin 2 (IL-2). It may act as a vaccine candidate for the development of therapeutic strategies against H. contortus infection. In this research, recombinant Hc8 (rHc8) and goat anti-rHc8 polyclonal antibodies were employed to evaluate the protective capacities of Hc8 antigen against H. contortus infections via active and passive immunization trials, respectively. In both trials, local crossbred female goats aged 9~12 months old were randomly divided into three groups, five in each group, respectively. Parasitological examinations, including fecal egg counts (FEC), cumulative FEC (cFEC), and worm burdens, were performed. Also, antibody levels in mucosal homogenate (MH) samples and hematological and immunological parameters were detected. In the passive trial, goats were intravenously immunized with 5 mg total IgG containing anti-rHc8 goat polyclonal antibodies. After twice immunization, compared with the challenged control group, cFEC was reduced by 39%. Also, there was a 46% reduction of worm burdens compared with the challenged controls. In the active immunization trials, 500 µg of recombinant Hc8 protein was given subcutaneously twice to 9~12 months-old local crossbred female goats with a two-week interval, resulting in the generation of high levels of antigen-specific circulating antibodies. Besides, cFEC and abomasal worm burden were reduced by 70% and 55%, respectively, compared with the challenged control group. In addition, immunized goats had higher mucosal homogenate IgA and hemoglobin levels than the challenged controls in both passive and active immunization trials. These preliminary results demonstrated the immunoprophylactic effects of Hc8 antigen and will inform new studies on ES proteins in developing subunit recombinant vaccines against H. contortus.